Os enviados de Dom Bosco entre os Masiripiwëiteri. O impacto missionário sobre o sistema social e cultural dos Yanomami ocidentais (Amazonas, Brasil) - Maria Inês Smiljanic (Journal de la Société des Américanistes)
Don Bosco’s messengers among the Masiripiwëiteri. Missionary impact on the social and cultural system of the western Yanomami (state of Amazonas, Brazil). This article describes the effects of Salesian missionary activities upon the Yanomami Indians who live in the Maturacá region in the Brazilian state of Amazonas. After decades of sedentarization, the missionaries altered the settlement pattern of the Masiripiwëiteri community, and encouraged the influx of newcomers from neighboring communities. In this way they inverted the group’s traditional reproduction dynamics. The Masiripiwëiteri were thus faced with the problem of having to transform potential enemies into co-residents which in turn meant they had to reshape their system of sorcery accusations. The replacement of cremation with burial also led to a drastic change in the Yanomami traditional funerary practices, causing the blurring of the spaces set up for the living and the dead, hence jeopardizing this fundamental opposition besides putting the Masiripiwëiteri in the position of having to resolve an insoluble problem of cosmological reconstruction.